2020
DOI: 10.1055/a-1159-4242
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Potential of Macamides Isolated from Yellow Tubers of Mashua (Tropaeolum Tuberosum)

Abstract: Although Tropaeolum tuberosum tubers have been consumed cooked as a folk remedy for the treatment of skin, lungs, liver and kidneys diseases, these uses have very limited scientific basis. Therefore, this article develops a phytochemical analysis of the yellow tubers of T. tuberosum with the objective to assess whether the isolated compounds have anti-inflammatory potential in the CCD-1109Sk, MRC-5 and RWPE-1 cell lines. We performed an extraction of T. tuberosum tubers using different organic solvents, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…subunit of the κB kinase inhibitor complex. 7,25 In this sense, we can indicate that the derivatives synthesised in this work lead to direct inhibition of IκB, preventing its degradation and the subsequent inhibition of NF-κB activation. 7,31 These results open the way to the development of new antiinflammatory drugs with a better safety profile compared to the drugs available on the market.…”
Section: Rsc Medicinal Chemistry Research Articlementioning
confidence: 69%
See 1 more Smart Citation
“…subunit of the κB kinase inhibitor complex. 7,25 In this sense, we can indicate that the derivatives synthesised in this work lead to direct inhibition of IκB, preventing its degradation and the subsequent inhibition of NF-κB activation. 7,31 These results open the way to the development of new antiinflammatory drugs with a better safety profile compared to the drugs available on the market.…”
Section: Rsc Medicinal Chemistry Research Articlementioning
confidence: 69%
“…24 The difference between derivatives 1e and 1f was not statistically significant ( ns p > 0.999) ( Table 1). Consequently, it was decided to use derivative 1f for subsequent modifications, since this macamide is found in a greater proportion in nature 25 and because it showed considerable biological activity (14.2 ± 1.47 μM).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the isolated macamides from Tropaeolum tuberosum, previous studies have concluded that N-benzyl oleamide and N-benzyl linoleamide (Figure 1) [14] The difference in pharmacological activity between N-benzyl oleamide and Nbenzyl linoleamide is due to the different number of double bonds of the fatty acid chain, [14,[17][18] being the N-benzyl linoleamide more active because of the additional double bond. This is because, as shown by mechanistic studies, the increase of double bonds in polyunsaturated fatty acids (PUFAs) leads to an increased activity in specific inflammatory disorders, through the interaction with the signalling pathway of JAK-STAT3 (Janus kinases/signal transducer and activator of transcription 3).…”
Section: Resultsmentioning
confidence: 99%
“…N-benzyl linoleamide is the most important, showing a higher anti-inflammatory activity when compared to other macamides. [14] Likewise, it has been indicated that this macamide is found in a higher proportion in relation to the other macamides which were isolated from the T. tuberosum tubers. [14] The objective of the present work is to synthesise different N-benzyl linoleamide analogues for the treatment of migraine (anti-inflammatory activity), making modifications to the characteristic fragments of the N-benzyl linoleamide.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation